Cover Picture: From Active‐Site Models to Real Catalysts: Importance of the Material Gap in the Design of Pd Catalysts for Methane Oxidation (ChemCatChem 9/2017). Issue 9 (10th May 2017) - Doan, Hieu A.; Sharma, Munish K.; Epling, William S.; Grabow, Lars C.
Abstract : The Front Cover visualizes the charge density difference in the transition state of methane activation over a single crystal Pd(1 0 0) surface. The charge density difference is projected onto the plane containing the carbon (grey) and hydrogen (white) atom of the dissociating methane molecule, and the closed palladium (blue) surface atom. In their Full Paper, H. A. Doan et al. demonstrate that such electronic structure simulations based on density functional theory predict a consistent trend for methane activation over metal‐promoted Pd surfaces, regardless of the active site model representation employed. The authors attribute the robustness of these catalytic trends to the locally confined charge density distribution in the transition state of the unimolecular methane dissociation step. More information can be found in the Full Paper by H. A. Doan et al. onpage 1594 in Issue 9, 2017 (DOI:10.1002/cctc.201601333 ).